Associations between breastfeeding intention, breastfeeding practices and post‐natal depression during the COVID‐19 pandemic: A multi‐country cross‐sectional study. Issue 1 (9th November 2022) - Chang, Yan‐Shing; Li, Kan M. C.; Chien, Li‐Yin; Lee, Eun Y.; Hong, Seo A.; Coca, Kelly P.
Abstract: Associations between breastfeeding intention, duration and post‐natal depression (PND) have been shown in pre‐COVID‐19 studies. However, studies during COVID‐19 have not examined the associations between breastfeeding intention, breastfeeding practices, and PND in an international sample of post‐natal women, taking into consideration COVID‐19 related factors. This is the first study to address this gap as both PND and breastfeeding may be affected by COVID‐19, and have important long‐term effects on women's and infant's health. A cross‐sectional internet‐based survey was conducted with 3253 post‐natal women from five countries: Brazil, South Korea, Taiwan, Thailand, and the United Kingdom from July to November 2021. The results showed that women who intended to breastfeed during pregnancy had lower odds of having PND than women who did not intend to. Women who had no breastfeeding intention but actually breastfed had greater odds (AOR 1.75) of having PND than women who intended to breastfeed and actually breastfed. While there was no statistical significance in expressed breast milk feeding in multivariable logistic regression models, women who had shorter duration of breastfeeding directly on breast than they planned had greater odds (AOR 1.58) of having PND than those who breastfed longer than they planned even after adjusting for covariates including COVID‐19‐related variables. These findings suggested the importance of working with women on their breastfeeding intention. Tailored support is required to ensure women's breastfeeding needs are met and at the same time care for maternal mental health during and beyond the pandemic. Key messages: This study identified independent associations of breastfeeding intention and actual breastfeeding practices with PND after adjustment for COVID‐19‐related covariates. Although women who intended to breastfeed during pregnancy were less likely to have PND, those who did not intend to breastfeed but did breastfeed were more likely to have PND than those who intended to breastfeed and breastfed. Women with shorter (vs. longer) than planned duration of breastfeeding on breast were more likely to have PND. Health care providers and policymakers should ensure tailored support is available for women's infant feeding plans and mental health.